Potensi Pengembangan Agrowisata Ngrowo Bening di Kota Madiun (Jurnal Agribisnis dan Agrowisata, 2026)
Potential for Development of Ngrowo Bening Agrotourism in Madiun City. Agrotourism is one type of tourism that has the potential to be developed in Indonesia. The use of vacant land in Ngrowo Bening has brilliant potential. The lack of promotion is one of the main causes of Ngrowo Bening agrotourism. The purpose of this study is to analyze the potential, constraints, and appropriate strategies to be applied to the development of Ngrowo Bening Agrotourism. The method used in this study is an analysis method using IFAS and EFAS tables then interprized in the SWOT and QSPM. The results of the analysis obtained on internal factors are the main strength, namely the existence of a green house that visitors can use as an educational tool (0.46). The main drawback is the lack of location compliance (0.90). The main potential is that it can help improve the economy (1.08). The main threat is unpredictable climatic conditions (1,32). The priority of the selected strategy is: to use green houses as a means of education. And the advice given by the author is that Ngrowo Bening Agrotourism requires investors to build facilities and the many levels of social media users should be used to provide interesting information and promotions.
Keywords: agrotourism; development strategy; SWOT; QSPM